1936
DOI: 10.1007/bf01909374
|View full text |Cite
|
Sign up to set email alerts
|

Die Abhängigkeit des Wachstums der Avena-Koleoptile und ihrer sogenannten Wuchsstoffproduktion vom Auxingehalt des Endosperms

Abstract: Einleitung.In einer kurzen Mitteilung babe ich darauf hingewiesen, dab der Wuchsstoff der Haferkoleoptile abh~ngig ist yore Wuchsstoffgehalt des Endosperms, und dab in der Koleoptfle kein Wuchsstoff neu gebildet wird. Diese Arbeit soll eine ausffihrliche Beschreibung der dort er-w~hnten Versuche bringen und meine frfiheren Darlegungen erweitern und beweisen.Der Gedanke, daI~ das Wachstum der jungen Keimpflanzen yon einer bestimmten Menge ,,Reservewuchsstoff" abh~ngt, wurde zuerst yon vA~ OV~.R]~]~K (1933) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1937
1937
1982
1982

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…It has been suggested that the seed of cereals supplies IAA to the shoot (8,17,19). The results indicate that there is no substantial acropetal supply of IAA, at least for the apical region of the mesocotyl, but there may be some supply to the basal region.…”
Section: And Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been suggested that the seed of cereals supplies IAA to the shoot (8,17,19). The results indicate that there is no substantial acropetal supply of IAA, at least for the apical region of the mesocotyl, but there may be some supply to the basal region.…”
Section: And Discussionmentioning
confidence: 87%
“…The primary leaves, for instance, appear able to supply relatively large amounts of IAA (10). There is also a possibility that the mesocotyl receives some IAA in free (8,17,19) or conjugated (6, 15) form from the seed. Ifregulation ofmesocotyl growth by IAA is to continue to be regarded as an example of hormone-mediated growth correlations, it is necessary, at least, to show that the IAA reaches it from elsewhere in the seedling.…”
mentioning
confidence: 99%
“…Seeds of Avena and Zea are known to be rich in auxin (Pohl, 1935(Pohl, , 1936Hemberg, 1955;Hamilton, Bandurski and Grigsby, 1961). The acidic ether-extractable fraction of Zea seeds contains IAA and other zones of auxin activity on chromatograms developed with ammoniacal isopropanol which are similar to those found in aqueous diffusates of coleoptile tips by Shen-Miller and Gordon; the major one has an i?p corresponding to that of P (Hemberg, 1958).…”
Section: Auxin In Guttation Fluidmentioning
confidence: 99%
“…Pohl (1935Pohl ( , 1936 produced evidence that the seed, which is rich in auxin, acted as a source of auxin which moved acropetally and accumulated at the coleoptile tip, but this possibility was rejected by Skoog (1937) who found that no auxin could be detected in agar blocks placed on the stumps of decapitated coleoptiles. He concluded that the seed was acting as the source of an auxin precursor which moved acropetally but that auxin itself did not move in this way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation